Emerging Trends in the Multimodal Nature of Cognition: Touch and Handedness - Ittyerah, Miriam (Frontiers in Psychology, 2017)
Advances in tactile cognition and haptics have increased our understanding of the multimodal nature of touch. Haptic data is mostly confined to human performance arising from the flexibility and dexterity of the fingers used to discriminate shapes and objects. Studies with infants indicate that recognition of objects either seen or held in the hand is possible during early periods of infancy. Evidence indicates performance differences between the hands decrease over periods of development, reflecting maturation of the cortical brain system supporting motor skills. Thus ability is not confined to the preferred hand. Tactile process and haptic cognition reflect hand ability. Studies examining manual performance must consider the relevance of haptics in research. Knowing about the evolution of the hands controlled by the cerebral hemispheres is of interest because it is a major contribution to the repertoire of human hand actions. The emergence of RDBM (role differentiated bimanual manipulation) is an important shift in the development of infant manual skills. Between 4 and 7 months of age, infants begin to manipulate objects using RDBM where one hand stabilized an object while the other hand manipulated the object. Understanding the affordance of a tool is an important cognitive milestone in early sensorimotor period that develops during the second year in full-term infants. This ability has also been demonstrated in preterm infants indicating the emergence of handedness during prenatal periods. Thus a multimodal approach that incorporates studies of tactile processes and hand actions may reveal their interactions with task demands and haptic ability.